2022
DOI: 10.1093/jcag/gwac014
|View full text |Cite
|
Sign up to set email alerts
|

Patient Experiences in the Management of Inflammatory Bowel Disease: A Qualitative Study

Abstract: Background Inflammatory bowel disease (IBD) can lead to substantial impairments of quality-of-life. Clinical guidelines and quality indicators aid physicians in practice but may not reflect the perspectives and experiences of patients with IBD. To address this, the objectives of this study were to understand patient experiences with IBD care and to explore priorities. Methods Based on a convenience sample of 36 participants, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…Similarities and differences were noted in comparing findings of the present study to those of our larger study (16). Similar findings included the barriers to receiving adequate care such as delayed diagnosis, long wait times for appointments, geographical and physical accessibility barriers, and physicians having insufficient knowledge of IBD, as well as inclusion of services provided by an ideal IBD clinic such as mental health support and non-traditional therapies.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Similarities and differences were noted in comparing findings of the present study to those of our larger study (16). Similar findings included the barriers to receiving adequate care such as delayed diagnosis, long wait times for appointments, geographical and physical accessibility barriers, and physicians having insufficient knowledge of IBD, as well as inclusion of services provided by an ideal IBD clinic such as mental health support and non-traditional therapies.…”
Section: Discussionsupporting
confidence: 86%
“…The present study was undertaken to increase our understanding of the health care concerns of patients with IBD with less than a university degree who may be at risk for poor health outcomes. This study is an add-on to a larger pan-Canadian study aimed at increasing our understanding of what patients want from their IBD health care providers (HCPs) to improve the delivery of equitable high-quality care (16).…”
Section: Introductionmentioning
confidence: 99%
“…Many patients expressed anxiety prior to arriving at a diagnosis and often could not access the care that they needed until they received a formal diagnosis. 24 During the waiting period, almost all participants turned to internet search platforms for information about the disease. Research has shown that a higher percentage of internet information originates from commercial organizations or pharmaceutical companies, and their sources may be inaccurate or even misleading.…”
Section: Discussionmentioning
confidence: 99%
“…A survey by the Canadian Medical Association suggests that individuals were satisfied with VC ( 92 ). Nationwide focus groups consisting of people with IBD offered insight into how they experienced VC ( 93 ). Telephone-based services were most common; many felt videoconferencing would have improved the interaction.…”
Section: Ehealthmentioning
confidence: 99%